1970
DOI: 10.3329/bjas.v38i1-2.9917
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Curing On The Quality Of Beef And Buffen

Abstract: The study was conducted to investigate the effect of curing on the quality of beef and buffen and also to find out the relationship between the quality of beef and buffen with their storage time. Six treatments of which three from beef were taken as dry salt cured beef (A 1 ), dry sugar cured beef (A 2 ), brine cured beef (A 3 ) and three from buffen as dry salt cured buffen (A 4 ), dry sugar cured buffen (A 5 ) and brine cured buffen (A 6 ). These samples were cured at room temperature for 10 days and then dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Furthermore, Baublits et al, (2006) reported palatability improvements in beef muscles while reducing the color degeneration induced by salt amplification. In another study, Islam et al, (2009) stated that brine curing is an effective process for beef preservation. Correspondingly, Sarker et al, (2021) concluded in the study that vinegar is efficient in short-term preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Baublits et al, (2006) reported palatability improvements in beef muscles while reducing the color degeneration induced by salt amplification. In another study, Islam et al, (2009) stated that brine curing is an effective process for beef preservation. Correspondingly, Sarker et al, (2021) concluded in the study that vinegar is efficient in short-term preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the kitchen salt (NaCl) is an additional material that is always used in cooking food (Purnomo, 1997). The addition of salt in processed foods is a preservation method that can extend the store life of processed food (Islam et al, 2009;Singh et al, 2010). It is reported that salt in processed foods provides an important role in improving flavor and taste characteristics (Weiss et al, 2010), palatability and consumer tastes (Liem et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is a high demand of beef and buffalo meat in Bangladesh due to its palatability and good flavours (Islam, 2008).…”
Section: Introductionmentioning
confidence: 99%